RE: Semi‑rigid ureteroscopy – Proximal versus distal ureteral stone - Kamarulzaman, Mohd Nazli (Wolters Kluwer - Medknow, 2016)
I read with great interest the article “Semi‑rigid ureteroscopy: Proximal versus distal ureteral stone” by Alameddine et al.[1] This article highlights important findings regarding common endourology procedure which is ureteroscopy. Since development of semi‑rigid ureteroscope, various studies had been done to evaluate the safety and efficacy of ureteroscopy. In this study, the authors found that stone‑free rate was comparable between proximal (89%) and distal (98.2%) ureteric stone with insignificant difference in complication rate. This study was retrospective in nature which had some limitations. The limitation found in this study was the selection of ureteroscope size. The authors stated that the ureteroscope size used ranged between 8 and 11 French.[1] These ranges were including almost all sizes of available ureteroscopes. Whereas, in other study by Molina Escudero et al., the ureteroscope size used was only 7 French.[2] These created a bias in this study. Without precise selection of the ureteroscope size, the author concluded that the use of smaller caliber semi‑rigid ureteroscopy combined with holmium‑yttrium‑aluminum‑garnet laser for proximal ureteral calculi is safe.[1] In my opinion, the conclusion made by the authors was not proved by this study.